A model of experiential shopping for the automotive industry: integrating the concepts of point of sale and multisensory marketing - Knaul, Philip (2014)
Research Problem – The car industry is undergoing significant shifts, as the market will experience more change within the next ten years than in the 50 years before. To approach customers with innovative concepts will become the omnipotent challenge for the manufacturers, while a brands’ success is closely connected to its point of sale presentation and communication. In fact, traditional marketing concepts turned into futile concepts, likewise customers seek for true experiences at all touch points and applications like multisensory-marketing have become the focal factor of success. Purpose of the Study – Despite the significance of innovative point of sale approaches, quantitative studies and coherent literature for the automotive industry have not been previously published or can’t be adapted adequately. Hence, the present dissertation strives to develop and test a theoretical model of experiential shopping, which integrates the concepts of point of sale and multisensory marketing equally. Design/Methodology/Approach – A quantitative baseline study (n=229) is stating the basis of the present study, in order to test the research hypothesis grounded on a literature review of secondary research. Descriptive- and multivariate analysis have been accomplished to infer meaningful results. Findings/Implications – In fact, customers are likely to benefit from cohesive point of sale materials, which are facilitating the buying process and enticing the shopper to the final purchase. Furthermore, different sensorial inputs impact the customers’ purchasing decision and intention to recommend the product and brand respectively. Research Limitations – Direction of future research and limitations of the actual study are present. The main limitation is the measurement of non-observable phenomena with a quantitative baseline study. The results have therefore to be reviewed within a field test of laboratory test, in order to verify behavioural issues.